Fundamentals of physiology A textbook for nursing students - Bijlani, RL; Bijlani, RL (New Delhi, India : Jaypee Brothers Medical Publishers (P) Ltd., 2001)
Fundamentals of Physiology helps nursing students to realize their true position. The book is highly specialized to meet the students of nursing who need to know a different set of facts. Compiled as per the syllabus of Nursing in various universities. Helps in easy understanding of the physiology of the human body.
Includes index.
Keywords: PHYSIOLOGY